The New Hunting Territory Debate: An Introduction to Some Unresolved Issues - Tanner, Adrian (Anthropologica, 2022)
Debates over the origin and nature of land tenure systems among Northern Algonquians, including hunting territories, have continued because various issues remain unresolved and also because these issues concern general theories of human social evolution. The debate has progressed from a "classic" phase, focused on the questions of origins, to a "postclassic" phase, concerned with the function and operation of hunting territories among precontact Algonquians. This essay will examine these issues in light of Marxist meanings for such terms as usufruct and various forms of private and communal property. It is proposed that we see the hunting territory system not as a single phenomenon but more as a structural form with variant manifestations.